Sprawa Mary Ellen Wilson i pierwsze amerykańskie organizacje na rzecz ochrony praw dziecka - Wojniak, Justyna (Biuletyn Historii Wychowania, 2023)
The paper presents the mechanisms that led to the first American legal regulations and organizations for the protection of minors and the elimination of child abuse. The background for the considerations is the case that shocked the American public opinion in the second half of the 19th century. It concerned a 10-year-old girl, Mary Ellen Wilson, who was a victim of violence and neglect on the part of her guardians. The attempts to save the child showed that the American system of social welfare lacked adequate institutional and organizational instruments to protect a child who was a victim of violence and abuse. Based on the literature and available archival materials – official documents and press publications from the discussed period – the course of the trial was reconstructed, as well as the initiatives undertaken after its completion, which led to the establishment of the first American organization aimed to protect children. The summary presents the characteristics of the American movement for the protection of children against the background of European initiatives undertaken in this field.